Clinical Trial on Computer-Aided Design in Pre-operative Alveolar Bone Grafting in Cleft Lip - Cleft Palate Patient - Krit Khwanngern (2020)
© 2019, Springer Nature Switzerland AG. Cleft lip and cleft palate are facial anomalies. One of the treatment for the patients is alveolar bone grafting. In Thailand, spiral CT scan has been extensively utilized in the diagnosis in order to examine the lesions on facial bone. However, spiral CT scans are expensive, relatively large and immobile. In this study, we evaluated the application of moveable CT scan. The important pre-operative information such as the shape of the alveolar cleft, the volume of the alveolar cleft, teeth, and tip of dental roots around alveolar cleft are required for treatment planning. Normally, plastic surgeons measured and evaluated these quantities in the operating room. Differently, the cleft lip and cleft palate patients underwent mobile CT for the pre-operative period. And with computer-aided design software, plastic surgeons worked collaboratively with engineers to process output and perform measurement pre-operatively. Our study shows that the pre-operative information from computer-aided design can increase understanding for alveolar cleft anatomy. The most important advantage of mobile CT and computer-aided design software is avoidance of dental root injury during alveolar bone graft operation.